Developing biodiversity indicators for African birds. Issue 1 (27th November 2017) - Wotton, S.R.; Eaton, M.A.; Sheehan, D.; Munyekenye, F. Barasa; Burfield, I.J.; Butchart, S.H.M.; Moleofi, K.; Nalwanga-Wabwire, D.; Ndang'ang'a, P.K.; Pomeroy, D.; Senyatso, K.J.; Gregory, R.D.
Abstract: Biodiversity indicators are essential for monitoring the impacts of pressures on the state of nature, determining the effectiveness of policy responses, and tracking progress towards biodiversity targets and sustainable development goals. Indicators based on trends in the abundance of birds are widely used for these purposes in Europe and have been identified as priorities for development elsewhere. To facilitate this we established bird population monitoring schemes in three African countries, based on citizen science approaches used in Europe, aiming to monitor population trends in common and widespread species. We recorded > 500 bird species from c. 450 2-km transects in Botswana, > 750 species from c. 120 transects in Uganda, and > 630 species from c. 90 transects in Kenya. Provisional Wild Bird Indices indicate a strong increase in bird populations in Botswana and a small decrease in Uganda. We also provide comparisons between trends of habitat generalists and specialists, of birds within and outside protected areas, and between Afro-Palearctic migrants and resident birds. Challenges encountered included recruiting, training and retaining volunteer surveyors, and securing long-term funding. However, we show that with technical support and modest investment (c. USD 30, 000 per scheme per year), meaningful biodiversity indicators can be generated and used in African countries. Sustained resourcing for the existing schemes, and replication elsewhere, would be a cost-effective way to improve our understanding of biodiversity trends globally, and measure progress towards environmental goals.